Analisis Video Pembelajaran Bilingual di Sekolah Dasar Terhadap Respon Peserta Didik - Nadila, Kania Yosa; Retnawati, Putri; Azizah, Nurul; Mayangsari, Arum; Devianti, Adella Najla; Ardhani, Christina Oktavida; Widagdo, Arif (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze bilingual learning at the elementary school level and to see students' responses to the method. Bilingual learning that integrates Indonesian and English is increasingly being applied in order to face global demands, but its implementation still faces various challenges, especially related to students' understanding of foreign languages. Through a descriptive qualitative approach, this study analyzed two bilingual learning videos used in two different elementary schools. The results of the analysis showed that students' responses were greatly influenced by the proportion of language use in the video. In classes dominated by Indonesian, students showed high active responses, such as answering questions and engaging in discussions. Meanwhile, in classes dominated by English, student engagement was lower and most students appeared passive. These findings emphasize the importance of balancing language use in bilingual learning so that students can understand the material well and feel confident to participate.